Microfluidic continuous flow digital loop-mediated isothermal amplification (LAMP). Issue 3 (28th November 2014) - Rane, Tushar D.; Chen, Liben; Zec, Helena C.; Wang, Tza-Huei
Abstract : A continuous flow droplet microfluidic device for digital nucleic acid detection using Loop-Mediated Isothermal Amplification (LAMP). Abstract : Digital nucleic acid detection is rapidly becoming a popular technique for ultra-sensitive and quantitative detection of nucleic acid molecules in a wide range of biomedical studies. Digital polymerase chain reaction (PCR) remains the most popular way of conducting digital nucleic acid detection. However, due to the need for thermocycling, digital PCR is difficult to implement in a streamlined manner on a single microfluidic device, leading to complex fragmented workflows and multiple separate devices and instruments. Loop-mediated isothermal amplification (LAMP) is an excellent isothermal alternative to PCR with potentially better specificity than PCR because of the use of multiple primer sets for a nucleic acid target. Here we report a microfluidic droplet device implementing all the steps required for digital nucleic acid detection including droplet generation, incubation and in-line detection for digital LAMP. As compared to microchamber or droplet array-based digital assays, the continuous flow operation of this device eliminates the constraints on the number of total reactions imposed by the footprint of the device and the analysis throughput caused by the time for lengthy incubation and transfer of materials between instruments.